A 3-Lie algebra and the dKP Hierarchy. Issue 1 (2nd January 2019) - Chen, Min-Ru; Chen, Ying; Yan, Zhao-Wen; Mei, Jian-Qin; Wang, Xiao-Li
Abstract : In terms of a 3-Lie algebra and the classical Poisson bracket { Bn, L } of the dKP hierarchy, a special 3-bracket { Bm, Bn, L } is proposed. When m = 0 or m = 1, the 3-lax equation is the dKP hierarchy and the corresponding proof is given. Meanwhile, for the generalized case ( m, n ), the generalized dKP hierarchy is also investigated.